Income, consumption and wealth inequality in Germany: Three concepts, three stories? - Charlotte Bartels; Carsten Schroeder (Forum for a New Economy, 2020)
Given how controversially inequality is still being discussed by both academics and policy makers in Germany, we discuss methodological issues related to the measurement of inequalities and review the literature and empirical estimates of different forms of inequality. One important issue is the choice of the measure of well-being: the central measures discussed are household equivalent disposable in-come, household consumption, and wealth. Subsequently we use the Income and Expenditure Survey (Einkommens- und Verbrauchsstichprobe (EVS)) for Germany since 1993 to compare inequality across income, consumption, and wealth. Generally, we find that these three concepts tell different stories about the level of inequality and its intertemporal pattern. In line with theoretical arguments and previous empirical evidence, wealth is more unequally distributed than income and income more une-qually than consumption.
Keywords: D; C21; D12; D31; 330; inequality; income; consumption; wealth